Rational Emotive Behavior Therapy untuk menurunkan perilaku melukai diri pada pasien dengan gangguan kecemasan umum - Defani Ismiriam Rakhmi (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
The subject is a 22 year old woman who is a victim of bullying. Subjects often think irrationally to solve problems without thinking about long-term consequences, one of which is doing self-injury. From the results of the assessment, the subject showed symptoms of Generalized Anxiety Disorder (GAD). The therapy applied to the subject is Rational Emotive Behavior Therapy (REBT) to reduce irrational thinking and maladaptive behavior. Therapy carried out in 6 sessions. The results of the intervention show that the subject can change irrational thinking to become rational. The subject may decide not to self-injure while solving the problem.